Evaluación de tres métodos para el cierre de heridas quirúrgicas en orquiectomía en caninos - Chacha Colcha, Jhorddy Rolando (2025)
This study was conducted at the Veterinary Clinic of the Universidad Estatal de Bolívar with the objective of evaluating three methods for closing surgical wounds in canine orchiectomies and determining the healing time when using adhesives, skin closure devices, and sutures. Additionally, the effect of the treatments on the postoperative behavior of the patients was analyzed. The study included 30 dogs, divided into three treatment groups with 10 animals each. The first group was treated with silk sutures (2/00), the second with adhesive skin closure devices (Zip Stitch), and the third with a tissue adhesive (Histoacryl®). On the third day after surgery, a sample was taken to determine the levels of C-reactive protein (CRP), and the wound healing process was monitored. Furthermore, a daily follow-up of postoperative behavior was carried out from the first day after surgery until the end of the study using an ethogram. The results showed differences in healing time between treatments. The group treated with skin closure devices had a shorter healing time compared to the other groups. Healing time with skin closure devices was three days, while the adhesive required five days and the sutures took eight days. However, no differences were observed in CRP levels between the different methods. Likewise, the postoperative behavior of the animals was not affected by any of the treatments. In conclusion, although the three closure methods did not show differences in CRP levels, the use of skin closure devices significantly accelerated the healing process, suggesting its potential as a more efficient option for closing surgical wounds in canine orchiectomies.